Effect of menopause and age on vascular impairment. (March 2023) - Aittokallio, Jenni; Saaresranta, Tarja; Riskumäki, Markus; Hautajärvi, Tiina; Vahlberg, Tero; Polo, Olli; Heinonen, Olli; Raitakari, Olli; Kalleinen, Nea
Highlights: Cardiovascular disease in aging women is a growing problem. 89 women initiated the study and 74 of them participated in the 10-year follow-up (from 46 till 56 years of age). We found early changes in cardiovascular risk factors and sleep-disordered breathing. Early signs of sleep-disordered breathing, obesity and impaired glucose control in middle age contribute to vascular decline in women even after 10 years. Abstract: Aims: The prevalence of cardiovascular diseases increases in women after menopause. The aim of the study was to determine the impact of conventional cardiovascular risk factors such as age, blood pressure, smoking, cholesterol, obesity, and glucose balance, but also menopausal state and sleep-disordered breathing on vascular impairment during menopausal transition. Methods: 89 women initiated the study and 74 of them participated in the 10-year follow-up. Cardiovascular disease risk factor assessments, ultrasound measurements of brachial artery function, including nitroglycerin-mediated vasodilatation and flow-mediated endothelium-dependent vasodilation, and sleep studies were repeated at baseline and at 5-year and 10-year follow-ups. Results: Over the study period, all the cardiovascular disease risk estimates increased. Both flow-mediated endothelium-dependent vasodilatation (decline 55 %) and nitroglycerin-mediated vasodilatation (decline 18 %) worsened over the 10 years ( p < 0.001). Vascular function was not associated with menopausal state (determined with follicle stimulating hormone). Systolic blood pressure ( p = 0.009) and smoking ( p = 0.006) at baseline were negatively associated with nitroglycerin-mediated vasodilatation at 5-year follow-up and the use of hormonal therapy at 5-year follow-up was positively associated with concurrent nitroglycerin-mediated vasodilatation ( p = 0.041). Intermittent nocturnal hypoxemia at baseline was associated with flow-mediated endothelium-dependent vasodilatation at 10-year follow-up ( p = 0.043). High body mass index and impaired glucose balance at 5-year follow-up were associated with nitroglycerin-mediated vasodilatation decline at 10-year follow-up ( p = 0.022 and p = 0.037, respectively). Conclusions: We demonstrate how cardiovascular risk factors and vascular function evolve during menopausal transition. Although menopause was not associated with vascular impairment, short-term improvement in vascular function was observed in those using menopausal hormonal therapy. Intermittent nocturnal hypoxemia, obesity and impaired glucose control are early predictors of vascular decline during postmenopause.